You are not logged in.

- Topics: Active | Unanswered

**altar****Member**- Registered: 2005-09-14
- Posts: 5

I decided to get back into learning how to solve these little problems that used to drive me mad when I was a kid. I found a website that explains problem solving by using an example BUT there's a fraction simplification I just don't understand.

The part I don't understand is the simplification of:

by_Faizah=m-(1/3m-4)/4-3 into m/6-2 If someone could explain that to me I'd be most grateful.

(I had to copy the entire image so sorry it's very long..)

Offline

**ganesh****Moderator**- Registered: 2005-06-28
- Posts: 20,747

by_Faizah=m-(1/3m-4)/4-3

This should be written as {[m-(1/3m-4)]/4}-3

= {[m - 1/3m +4]/4}-3

= {[2/3m+4]/4}-3

= {[(2m+12)/3]/4}/ - 3

= {[2m+12]/12} - 3

= {[2m+12]-36}/12

= {2m - 24}/12

= m/6 - 2

It is no good to try to stop knowledge from going forward. Ignorance is never better than knowledge - Enrico Fermi.

Nothing is better than reading and gaining more and more knowledge - Stephen William Hawking.

Offline

**altar****Member**- Registered: 2005-09-14
- Posts: 5

Thanks I think I got it, but I must work on my algebra. m-1/3m = 2/3m is so obvious but my brain refuses to see it.. aaah my head!

Offline

**altar****Member**- Registered: 2005-09-14
- Posts: 5

just a little question here,

you wrote:

= {[2m+12]/12} - 3

= {[2m+12]-36}/12

= {2m - 24}/12

= m/6 - 2

Would the following be correct also?

= {[2m+12]/12} - 3

= [2m/12] +1-3

= m/6 - 2

?

Offline

**ganesh****Moderator**- Registered: 2005-06-28
- Posts: 20,747

It is no good to try to stop knowledge from going forward. Ignorance is never better than knowledge - Enrico Fermi.

Nothing is better than reading and gaining more and more knowledge - Stephen William Hawking.

Offline

**altar****Member**- Registered: 2005-09-14
- Posts: 5

How about this one?

= {m - [1/3m -4] - [m/6 -2] /2} -2

The result is given: m/4+1

= {m - [1/3m -4] - [m/6 -2] /2} -2

= { 2/3m +4 - [m/6 -2] /2} -2

= { 2/3m +4 - [m/6 -12/6] /2} -2

= 2/6m +2 - [m/12 +12/12] -2

= 4/12m +2 - m/12 +1 -2

= m/4 +1

Was that right? (I always get some sign changes wrong..)

Offline

**ganesh****Moderator**- Registered: 2005-06-28
- Posts: 20,747

altar wrote:

How about this one?

= {m - [1/3m -4] - [m/6 -2] /2} -2

The result is given: m/4+1

= {m - [1/3m -4] - [m/6 -2] /2} -2

= { 2/3m +4 - [m/6 -2] /2} -2

= { 2/3m +4 - [m/6 -12/6] /2} -2

= {2/3m +4 - m/12 +1}-2

= {2/3m - m/12 + 5} - 2

= 11/12m + 5 - 2

= 11/12m + 3

= (11m+36)/12

It is no good to try to stop knowledge from going forward. Ignorance is never better than knowledge - Enrico Fermi.

Nothing is better than reading and gaining more and more knowledge - Stephen William Hawking.

Offline

**altar****Member**- Registered: 2005-09-14
- Posts: 5

Thanks a lot

Offline

**i need help****Guest**

There are three houses in a row and in the other side there are three fountains, each house must take water from each fountain without the pipes intersecting. The problem must be solved in two dimensions.

**kylekatarn****Member**- Registered: 2005-07-24
- Posts: 445

i need help wrote:

There are three houses in a row and in the other side there are three fountains, each house must take water from each fountain without the pipes intersecting. The problem must be solved in two dimensions.

Check your other post.

Offline

**kenner101****Guest**

WeLl,

i KiNdA' gEt It BuT nOt mUcH!!!!!!!!!!!!!!!!!!!!!

**hope****Guest**

altar wrote:

I decided to get back into learning how to solve these little problems that used to drive me mad when I was a kid. I found a website that explains problem solving by using an example BUT there's a fraction simplification I just don't understand.

The part I don't understand is the simplification of:

by_Faizah=m-(1/3m-4)/4-3 into m/6-2 If someone could explain that to me I'd be most grateful.

(I had to copy the entire image so sorry it's very long..)

http://www.hawaii.edu/suremath/k4_12dir … mints1.GIF